Unlocking the Potential of Education in Nigeria's Industry 4.0 Era: Overcoming Challenges of Digital Transformation - Adeoye, Moses Adeleke; Akinnubi, Olaolu Paul; Yahaya, Ajoke Kudirat (Universitas Pendidikan Ganesha, 2023)
The introduction of Industry 4.0 has led to enormous technology advancements that have altered many different industries throughout the world. As Nigeria struggles to stay up with the digital revolution, it faces numerous educational obstacles. The primary obstacles to the successful implementation of digital transformation in the Nigerian educational system are examined. This study aims to analyze the importance of fostering partnerships between governmental bodies, business executives and academic institutions. The research method uses Systematic Literature Review (SLR). The data collection process is carried out by identifying and evaluating scientific articles that are relevant to the topic. After identifying relevant articles, the data analysis process began by thoroughly reading each selected article. The study found collaboration can make it easier to share information, resources and expertise, creating environment for the digital revolution of education. In conclusion, Nigeria must overcome several obstacles to fully realize the potential of education in the age of Industry 4.0. By investing in infrastructure, teacher training, curriculum development, collaborations, research, and inclusivity, Nigeria may embrace the promise of digital transformation to enhance its educational system and prepare its future workforce for the demands of the digital era.